Research Methods for Business: a skill-building approach (Seventh Edition) - Sekaran, Uma, Bougie, Roger (Hohn Wiley & Sons, 2016)
The seventh edition has fully revised and updated to include cutting-edge examples and enriched pedagogiccal features desaigned to improve student learning outcomes. This is now an encreased amphasis on the relationship between the scientifics and the paragmatic approaches to researc, while the key concept are explored and applied to real-life research throughout the book.